2022
DOI: 10.5863/1551-6776-27.7.655
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Patient-Specific Aminoglycoside Monitoring for Treatment of Pediatric Cystic Fibrosis Pulmonary Exacerbations

Abstract: OBJECTIVE Aminoglycosides are frequently used for empiric and definitive treatment of cystic fibrosis (CF) pulmonary exacerbations. Various methods have been described for aminoglycoside therapeutic drug monitoring. The objective of this study is to evaluate the effect of patient-specific pharmacokinetic calculations for aminoglycosides used to treat CF pulmonary exacerbations. METHODS Ambidirectional cohort study of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…There was no significant difference between groups for change in ppFEV1, antibiotic duration, length of stay, or nephrotoxicity. 20 In the patient-specific PK group, 75% of participants required dose adjustments after initial measurement of serum concentration, whereas none of those in the trough-only group required dose adjustments (p < 0.001); the majority of adjustments involved a decrease in dose interval to avoid a prolonged drug-free interval. 20…”
Section: Aminoglycosidesmentioning
confidence: 92%
See 3 more Smart Citations
“…There was no significant difference between groups for change in ppFEV1, antibiotic duration, length of stay, or nephrotoxicity. 20 In the patient-specific PK group, 75% of participants required dose adjustments after initial measurement of serum concentration, whereas none of those in the trough-only group required dose adjustments (p < 0.001); the majority of adjustments involved a decrease in dose interval to avoid a prolonged drug-free interval. 20…”
Section: Aminoglycosidesmentioning
confidence: 92%
“…Of the 4030 records identified in the initial search, 1 study 18 met the inclusion criteria (Figure 1); 2 additional studies were identified in the subsequent search. 19,20 The characteristics of included studies are summarized in Table 1.…”
Section: Aminoglycosidesmentioning
confidence: 99%
See 2 more Smart Citations